Analisis Perubahan dan Pemanfaatan Lahan Perkebunan Menjadi Sektor Perindustrian di Boyolali terhadap Aspek Ekologi, Ekonomi, dan Sosial Budaya - Anisa Eka Putri; Aisyah Aida Riadi; Ardia Candra Fajar Herbowo; Ayu Intan Aftsari; Daffa' Nur Waskito; Agung Hidayat; Muhammad Amin Sunarhadi (Center for Environmental Research, LPPM, Universitas Sebelas Maret, 2025)
The increase in industrial areas located in Butuh Village, Mojosongo District, Boyolali Regency has a significant impact on land use. This is because changes in industrial land have disrupted agricultural and plantation activities which are still actively producing. This change in land use was due to an increase in the mobilization of the population in the village of Need, the socio-economic conditions of agriculture, and government policies related to changes in land use. This study aims to determine the condition of changes in land use through remote sensing digital imagery. The method used in this study is an overlay technique using ArcGIS with Geographic Information System (GIS) analysis. The analysis method used is spatial analysis and statistical analysis with a qualitative method approach. After a comparison was made with the overlay technique on Google Earth between 2009 and 2020, there was a significant change in land use